Analisis Keberlanjutan Usahatani Kopi Organik di Kecamatan Arjasa Kabupaten Situbondo - Iqlima Liyusak Al Islami; Puryantoro Puryantoro; Andina Mayangsari (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
One of the agricultural commodities that is very significant in boosting the country's economy is coffee. Kayumas Village is the largest coffee-producing area in Situbondo Regency. Kayumas Village can potentially develop organic coffee with some of the already certified organic land. Organic coffee is coffee that is produced using organic methods such as using organic fertilizer. Coffee farming in Kayumas Village is still entirely sustainable. This research aimed to determine the index and sustainability status of organic coffee farming in Kayumas Village, Arjasa District, Situbondo Regency. This research can provide information for farmers on the sustainability of coffee farming and can be a consideration for the government in making better policies regarding coffee farming. The study was conducted in 2023 by collecting data using survey and observation methods. Sampling used a saturated sampling technique because the sample was less than 30 people; the sample used was all 20 members of the Kelompok Tani Sejahtera. The analysis method used is Multidimensional Scaling (MDS), which uses the Rap-Coffe approach to see the sustainability status in Kayumas Village. There are five variables used in this research, namely ecological dimensions, economic dimensions, social dimensions, institutional dimensions, and infrastructure and technology dimensions. Each dimension has several attributes assessed to obtain a sustainability index value. The results showed that the ecological and economic dimensions are in the sustainable category, while the social and institutional dimensions and infrastructure and technology dimensions are in the moderately sustainable category. The most sensitive attributes to the sustainability of organic coffee in Kayumas Village in each dimension are (a) the ecological dimension, namely waste disposal; (b) the economic dimension, namely income outside coffee farming; (d) the social dimension, i.e., the average age of farmers; (e) institutional dimension, namely participation in farmer groups; (f) the dimensions of infrastructure and technology, namely the availability of agricultural processing industries.